An Investigation of English Language Teachers’ Attitude toward the Use of Technology in Languange Teaching at SMA 3 Parepare - Herni Tri Handayani; Arqam Arqam; Magdahalena Tjalla; Mujahidah Mujahidah; Abdul Haris Sunubi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Teachers’ attitudes play a role in shaping the educational environment and influencing student learning outcomes. They encompass their beliefs, values, and behaviors toward their profession, students, colleagues, and the learning process. The research aimed to Investigate English language teachers’ Attitudes toward the Use of Technology in Language Teaching at SMA 3 Parepare. This research used descriptive qualitative research with a study cases approach, there were three English teachers with observe the English language teaching and learning process and the interview process used semistructured interviews and the analysis technique used data reduction, display data, and conclusion. The result of this research was as follows: 1) English language teachers’ attitude toward teaching English focused on instructional method and active interaction with group discussions and multimedia-enhanced lessons proved the contribution to creating a practical English language learning experience for students. 2) English language attitude toward the use of Technology showed a positive attitude toward technology which utilize technological tools such as LCD, computers, and interactive whiteboards to enhance lessons effectively. 3) English language teachers’ implementation toward the use of technology engaging learning experiences by incorporating multimedia resources, project-based learning, and interactive conversations to stimulate student interest and participation while enhancing students’ language skills but also fosters creativity, using technology effectively and create an innovative learning environment at class